In Scripture : the first stories of Jewish sexual identities - Lefkovitz, Lori Hope, 1956- (Rowman & Littlefield Publishers, 2010)
Applying psychoanalytic and gender theory to selected Biblical narratives from Genesis to the Book of Ruth, Lefkovitz interprets the Bible's stories as foundation texts in the development of sexual identities. In Scripture is an exploration of the Biblical origins of a series of unstable ideas about the sexes, human sexuality, family roles, and Jewish sexual identities, in particular, and by extension, changing attitudes towards Jewish men and women.